Whole exome analysis of primary immunodeficiency - E. S. Rahmani; Н. Azarpara; M. Karimipoor; Н. Rahimi (Вавиловский журнал генетики и селекции)
The human primary immunodeficiency diseases (PIDs) refer to a rare heterogeneous group of single-gene inherited disorders causing malfunctions in the immune system, and thus the affected patients have a predisposition to severe life-threatening infections. The heterogeneous nature of PIDs, which involves at list 300 different genes, makes diagnosis of the disease a complex issue. Although studies revealed that six million people have a kind of PID, but due to a complex diagnosis procedure many affected individuals have not gotten a correct diagnosis. However, thanks to advancing in the DNA sequencing method and availability of sophisticated sequencers molecular characterization of genetic disorders have been revolutionized. The whole exome sequencing (WES) method can help clinicians detect Mendelian disease and other complex genetic disorders. The presented study used WES to investigate two infants with symptoms of primary immunodeficiency including hemophagocytic lymphohistiocytosis (HLH) and severe combined immunodeficiency (SCID). It has been shown that the HLH patient had a mutation in the UNC13D gene (NM_199242.2:c.627delT), and the SCID patient had a mutation in the RAG1 gene (NM_000448.2:c.322C>G). It has been demonstrated that WES is a fast and cost-effective method facilitating genetic diagnosis in PID sufferers.